Using virtual reality for industrial design learning: a methodological proposal. Issue 11 (1st November 2016) - Jimeno-Morenilla, Antonio; Sánchez-Romero, José Luis; Mora-Mora, Higinio; Coll-Miralles, Rafael
ABSTRACT: Nowadays, the different computer tools available enable designers to create complex industrial prototypes. The use of these tools is constrained by the limitations imposed by common devices, such as screens and displays. Recently emerged virtual and augmented reality techniques have started being used as supports in many learning and industrial environments. Beyond the new possibilities that these tools offer for designing industrial objects, the underlying question is whether these new technologies could improve the creativity of designers to enable them to get a better understanding of the designing process itself. This paper presents a methodological proposal for the deployment of an industrial design engineering course aimed not only at learning different design techniques, but also at assessing the creativity skills of students. The practical contents include the use of virtual reality devices, to help the designer overcome the limitations of prototype visualisation and make better designing decisions. Moreover, a creativity test will be performed at the beginning and at the end of the course to assess the changes in creativity skills taking place within the experiment group versus the changes in a traditional learning (control) group.